2018
DOI: 10.1007/s00264-018-3951-6
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of sagittal osteotomy inclination and the anteroposterior translation in medial open-wedge high tibial osteotomy—one of the causes affecting the patellofemoral joint?

Abstract: High rates of anterior-inclined osteotomy have been described previously as well as in this study. Anterior-inclined osteotomy tends to result in the anterior translation of the proximal fragment. This may result in increased vertical vector force onto the patellofemoral joint, which further accelerates patellofemoral joint degeneration. Therefore, surgeons should attempt to perform parallel osteotomy or avoid anterior displacement of the proximal fragment if there is concern of anterior-inclined osteotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…An increase in the posterior tibial slope could cause anterior translation of the tibia and increase the load on the anterior cruciate ligament [11,12]. An increased posterior tibial slope could also cause a redistribution of pressure into the posterior tibia in the anterior cruciate ligament-deficient knee, causing degenerative changes in articular cartilage [13] and an increase of vertical vector force onto the patellofemoral joint, which could lead to osteoarthritis of the patellofemoral joint [14,15]. In addition to the knee joint, it has been reported that the tibial slope also has important biomechanical implications on the ankle joint [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the posterior tibial slope could cause anterior translation of the tibia and increase the load on the anterior cruciate ligament [11,12]. An increased posterior tibial slope could also cause a redistribution of pressure into the posterior tibia in the anterior cruciate ligament-deficient knee, causing degenerative changes in articular cartilage [13] and an increase of vertical vector force onto the patellofemoral joint, which could lead to osteoarthritis of the patellofemoral joint [14,15]. In addition to the knee joint, it has been reported that the tibial slope also has important biomechanical implications on the ankle joint [31].…”
Section: Discussionmentioning
confidence: 99%
“…The increase in posterior tibial slope of the tibiofemoral joint leads to anterior translation of the tibia relative to the femur, thus developing an overload on the anterior cruciate ligament [11,12]. An increased posterior tibial slope of the tibiofemoral joint could also cause a redistribution of pressure into the posterior tibia in the anterior cruciate ligamentdeficient knee, resulting in degenerative change in articular cartilage [13] and an increase of vertical vector force onto the patellofemoral joint, which could lead to osteoarthritis of the patellofemoral joint [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Patellofemoral joint problems after OWHTO may be due to anterior translation of the proximal tibial fragment [36] or to medial patellar tilt increasing lateral patellofemoral pressure [37]. In contrast, a recent study with a mean 3 years' follow-up found no deterioration in patellofemoral cartilage associated with decreased patellar height [38].…”
Section: Discussionmentioning
confidence: 97%
“…So, partial patellectomy was usually employed in treating CMP. Tibial tuberosity surgeries, consisting mainly of the tibial tuberosity osteotomy, tibial tuberosity anteversion, and tibial tuberosity elevation, by restoring the biomechanical force line of the patellofemoral joint could improve joint function, but it will promote the degeneration of PFJ to a certain extent [31]. Harrington et al reported that the McKeever patellar resurfacing prosthesis showed a beneficial long-term effect in the treatment of severe CMP, which is usually as a salvage procedure for advanced PFJOA [32].…”
Section: Surgical Treatmentmentioning
confidence: 99%